(3SLY GdeWhbs - (3eMeO Hf eMeO Hf eMeO Hf GdMSf GdLPGej GdaGQbj GdeUQj, GHf fHGJg , LeGd GdOjf CHh HcQ,J (B768 (3g` s
(3ChdgG (B:s
(3hHYO agPg GhQGb JKeQ GdTcQ HehLH LeYgG GdPi JLeY Ydjg GdCdHdGH , SHH fXegG , hdGHO ddfXe ef CSHGH s
(3BNQgG (B:s
(3dGjfcQ GdeYThb ai LfOg Oe GdTgjO GdUGHQ GdeZQe hGdQjM QjM GdeSc HGOceG SeYJe hGddhf dhf GdOe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3fSNI KGfjIs
(3JJab aij ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa HYV GdCdaGX s
(3HChdgG JedcGJ eDQNI (B1213 (3g` s
(3cJHJ GdYfhGfGJ HGdMeQI s
(3hJdG BNQgG bUjOI WhjdI ai eOM GdQShd Udi Gddg Ydjg hSdes
(3bQf GdfSN (B:s
Keywords: (3GdCOHs